Investigating Sources of Conflict in Deep Phylogenomics of Vetigastropod Snails. (18th October 2021) - Cunha, Tauana Junqueira; Reimer, James Davis; Giribet, Gonzalo
Abstract: Phylogenetic analyses may suffer from multiple sources of error leading to conflict between genes and methods of inference. The evolutionary history of the mollusc clade Vetigastropoda makes them susceptible to these conflicts, their higher level phylogeny remaining largely unresolved. Originating over 350 Ma, vetigastropods were the dominant marine snails in the Paleozoic. Multiple extinction events and new radiations have resulted in both very long and very short branches and a large extant diversity of over 4000 species. This is the perfect setting of a hard phylogenetic question in which sources of conflict can be explored. We present 41 new transcriptomes across the diversity of vetigastropods (62 terminals total), and provide the first genomic-scale phylogeny for the group. We find that deep divergences differ from previous studies in which long branch attraction was likely pervasive. Robust results leading to changes in taxonomy include the paraphyly of the order Lepetellida and the family Tegulidae. Tectinae subfam. nov. is designated for the clade comprising Tectus, Cittarium, and Rochia . For two early divergences, topologies disagreed between concatenated analyses using site heterogeneous models versus concatenated partitioned analyses and summary coalescent methods. We investigated rate and composition heterogeneity among genes, as well as missing data by locus and by taxon, none of which had an impact on the inferred topologies. We also found no evidence for ancient introgression throughout the phylogeny. We further tested whether uninformative genes and over-partitioning were responsible for this discordance by evaluating the phylogenetic signal of individual genes using likelihood mapping, and by analyzing the most informative genes with a full multispecies coalescent (MSC) model. We find that most genes are not informative at the two conflicting nodes, but neither this nor gene-wise partitioning are the cause of discordant results. New method implementations that simultaneously integrate amino acid profile mixture models and the MSC might be necessary to resolve these and other recalcitrant nodes in the Tree of Life. [Fissurellidae; Haliotidae; likelihood mapping; multispecies coalescent; phylogenetic signal; phylogenomic conflict; site heterogeneity; Trochoidea.]